Peixes de costão rochoso: Reserva Biológica Marinha do Arvoredo (Brasil) e arquipélago dos Açores (Portugal) - Andrade, Áthila Bertoncini (Universidade Federal de São Carlos, 2009)
The success of a Marine Protected Area relies strongly on how well they meet their management goals. The Arvoredo Marine Biological Reserve (AMBR) lies in the southernmost limit of reef fishes occurrence in the Southwestern Atlantic. An updated checklist of shallow coastal fish species of the AMBR archipelago, with 15 new records is presented with comments on rare and threatened species. A total of 203 species belonging to 133 genera and 68 families and 17 orders was observed during the four-year monitoring the rocky reef fish in areas inside and outside the AMBR, through underwater visual censuses. The richest families were Carangidae, Serranidae, Labridae, Scaridae and Gobiidae. All comparisons significantly favoured communities inside the AMBR, except for diversity that was not significantly different. Haemulon aurolineatum was the most abundant species in all six sites, being Stegastes fuscus the most frequent. Invertebrate feeders dominated the areas, followed by omnivores in relative abundance. The analysis of how selected target species benefit from the protection effect did not show a clear pattern of significant increases in abundances along the sampled years. The same methodology was applied to investigate the community structure of shallow rocky reef fish fauna of the Azores Archipelago. A total of 52 fish species from 26 different families was observed. Trophic categories are given for observed species with comments on distribution and densities along sampled depth strata. Sparidae, Labridae and Carangidae were the most speciose families, being Diplodus sargus, Pagellus acarne and Coris julis, the most abundant species that consequently also accounted to the highest densities. Mean densities along sampled strata were tested for significant differences. Cleaning interactions among the rainbow wrasse Coris julis and the azorean blue wrasse Centrolabrus caeruleus are presented, as well as, comments on the exotic species Diplodus vulgaris, observed foraging among schools of small sized Labrids. In the case of AMBR, while surveillance of poaching, development and implementation of long-term educational programs, as well as, efforts to improve enforcement do not overcome the status of minimal, the AMBR will continue far from completing its fundamental objectives of protecting the rich ecosystem it shelters.
Keywords: Peixe; Ecologia marinha; Reservas biológicas; Peixe marinho; CIENCIAS BIOLOGICAS::ECOLOGIA